Comparison of reduction sugar analysis method in cilembu sweet potato (Ipomoea batatas l.) using luff schoorl and anthrone method - Taufik, Irfan Imam; Guntarti, Any (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2016)
Background: Cilembu Village - Sumedang, West Java is the producer of sweet potato that tastes sweet. The sweet taste was obtained from potato that has been through the process of incubation for 3 weeks, with a result of the change of starch by amylase enzyme into reducer sugars in the sweet potato Cilembu. Objective: The aim of the study is to verify the levels of reducer sugar of sweet potato Cilembu the analysis of reducer sugar itself is required and the comparison of the methods used. Methods: Among many calorimetry methods that used to analyze reducer sugar, the most widely used is Anthrone. The analysis of total carbohydrates, especially reducer sugar is quite simple and sensitive. but the analysis method for reducer sugar is quite simple SNI 3457.1:2008 using Luff Schoorl method that based on titrimetric, it is consuming time, difficult to do for untrained analyser and the reduction reaction is not stoikiometric. the candidate method that using Anthrone method is recommended in order to replace Luff Schoorl method of reducing sugar in SNI 3457.1:2008. Results: The average levels of reducer sugar in sweet potato Cilembu that used Luff Schoorl as a method was 14.88 ± 0.44 (%) whereas Anthrone method was 21,60 1,31 (%). The average levels of reducer sugars in sweet potato Cilembu from Luff Schoorl method completed the Indonesia Pharmacopoeia conditions, that is has a recovery value a 92,49 % % and but has 3,25% CV value. The average levels of reducer sugar in sweet potato Cilembu with Anthrone method did not complete the Pharmacopoeia Indonesia conditions, which has a recovery value a 67,58 % and has CV 6,56 % value. Conclusion: Anthrone method not recommended for analyze the reducer sugars in sweet potato Cilembu.